Alkylpotassium-Catalyzed Benzylic C–H Alkylation of Alkylarenes with Alkenes - Sato, Io; Yamashita, Yasuhiro; Kobayashi, Shū (Synthesis, 2019)
Catalytic benzylic C–H alkylation reactions of alkylarenes with alkenes such as β-substituted styrenes and vinylsilanes have been achieved by utilizing alkylpotassium as a catalyst. Various substituted toluene derivatives can be alkylated under mild reaction conditions to afford the desired functionalized hydrocarbons in moderate to high yields.
Keywords: strong base; alkylarene; alkylation; alkylpotassium; alkene